Teknik Distraksi Guided Imagery sebagai Alternatif Manajemen Nyeri pada Anak saat Pemasangan Infus - Nopi Nur Khasanah; Indra Tri Astuti (Jurnal Kesehatan, 2017)
The infusion procedure was the first invasive treatment in Emergency Room (ER) to fulfill the need of fluid and electrolyte. Nurses need to used the right method to decrease pain worst in children when having procedure infusion. The aim of this study was to analyze the differences in children pain score when having procedural infusion with guided imagery, ethyl chloride, and deep breathing techniques. This study used quasi-experiment with post-test treatment, 45 children as a participant by consecutive sampling techniques. The data was collected using Wong-Baker face pain rating scale and analyzed by Kruskal-Wallis test. The result showed that ρ value was 0,338 (ρ>0,05), in which can be concluded that there are no significant differences on three intervention. The guided imagery could be used as an alternative pain management on children when having a procedure of infusion at ER.